2015
DOI: 10.18632/oncotarget.5577
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and inactivation of PTEN at residues Ser380/Thr382/383 induced by Helicobacter pylori promotes gastric epithelial cell survival through PI3K/Akt pathway

Abstract: Phosphorylation of PTEN at residues Ser380/Thr382/383 leads to loss of phosphatase activity and tumor suppressor function. Here, we found that phosphorylation of PTEN at residues Ser380/Thr382/383 was increased with gastric carcinogenesis, and more importantly, Helicobacter pylori was a trigger of this modification in chronic non-atrophic gastritis. H. pylori could phosphorylate and inactivate PTEN in vivo and in vitro, resulting in survival of gastric epithelial cells. Furthermore, stable expression of domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 42 publications
5
64
0
Order By: Relevance
“…Previously, numerous oncogenic signaling pathways, including the PI3 kinase‐AKT, β‐catenin‐WNT, Hedgehog/GLI, ERK‐MAPK, JNK, and NF‐κB pathways, have been studied and demonstrated to be involved in H. pylori pathogenesis . In this study, we confirmed that some of those signaling pathways are involved in H. pylori ‐associated gastric cancer, such as focal adhesion, Th1 and Th2 cell differentiation, Th17 cell differentiation, bacterial invasion of epithelial cells, epithelial cell signaling, and the NF‐κB and Hedgehog signaling pathways.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Previously, numerous oncogenic signaling pathways, including the PI3 kinase‐AKT, β‐catenin‐WNT, Hedgehog/GLI, ERK‐MAPK, JNK, and NF‐κB pathways, have been studied and demonstrated to be involved in H. pylori pathogenesis . In this study, we confirmed that some of those signaling pathways are involved in H. pylori ‐associated gastric cancer, such as focal adhesion, Th1 and Th2 cell differentiation, Th17 cell differentiation, bacterial invasion of epithelial cells, epithelial cell signaling, and the NF‐κB and Hedgehog signaling pathways.…”
Section: Discussionsupporting
confidence: 80%
“…and signaling pathways (PI3 kinase‐AKT, β‐catenin‐WNT, and NF‐κB pathways, etc.) were confirmed to play an important role in H. pylori pathogenesis . However, a database‐based comprehensive analysis of genes and signaling pathways involved in H. pylori pathogenesis is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, H. pylori might interfere with the survival pathways, especially PI3‐kinase/Akt. The involvement of phosphatase PTEN (phosphatase and tensin homolog) in the regulation of PI3‐kinase/Akt upon H. pylori infection is shown in the publication of Yang et al . They observed in gastric tissue a loss of PTEN activity due to a decrease in its expression and a parallel hyperphosphorylation, resulting in an increase in Akt survival activity.…”
Section: Apoptotic and Anti‐apoptoticsignalingmentioning
confidence: 97%
“…On the other hand, H. pylori might interfere with the survival pathways, especially PI3-kinase/ Akt. The involvement of phosphatase PTEN (phosphatase and tensin homolog) in the regulation of PI3-kinase/Akt upon H. pylori infection is shown in the publication of Yang et al53 They observed in gastric tissue a loss of PTEN activity due to a decrease in its expression and a parallel hyperphosphorylation, resulting in an increase in Akt survival activity.13 | CHANGES IN DNA METHYLATION UPON H. PYLORI INFECTIONDNA methylation in promoter regions is known as a regulatory mechanism controlling gene activity. This epigenetic control of host gene expression is not only important in development and differentiation, but also in the formation of cancer.…”
mentioning
confidence: 99%
“…For example, H. pylori has a profound effect on N-Myc downstream-regulated gene 2 ( NDRG2 ) promoter methylation; methylation was seen in 54% of primary gastric cancer specimens [17*]. NDRG2 is a potential tumor suppressor that aids in dephosphorylation of the phosphatase and tensin homolog (PTEN) [18]; PTEN is frequently found inactivated in gastric cancers due to increased levels of C-terminal phosphorylation [19]. In the active, unphosphorylated form, PTEN dephosphorylates PIP3, which results in decreased PI3K/Akt activity [18, 20].…”
Section: Introductionmentioning
confidence: 99%